Deep Learning: An Analysis of Science Education Aproaches on Student Learning Outcomes - Riza Maulida; Muhammad Azhari; Maya Agustina; Gamal Barqie; Wan Marfazila Binti Wan Mahmud (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The implementation of the deep learning approach in science education is still facing challenges, particularly in terms of teachers’ understanding, readiness, and the availability of supporting facilities. In many cases, learning practices are still dominated by rote memorization, which limits students’ conceptual understanding and critical thinking skills. Therefore, this study aims to analyze teachers' perceptions of the implementation of the deep learning approach in science education at MIN 8 Aceh Barat. This study used a descriptive quantitative approach with data collected through questionnaires and interviews involving science teachers who have experience in applying the deep learning approach. The data were analyzed using descriptive percentage techniques with a Likert scale to examine teachers’ understanding, readiness, and supporting and inhibiting factors. The results showed that teachers generally have positive to very positive perceptions of the implementation of deep learning, with most responses exceeding 75%. Teachers consider this approach more effective than rote learning as it enhances student engagement, strengthens conceptual understanding, and facilitates the connection between scientific concepts and real-life contexts. In terms of readiness, teachers are fairly prepared to implement this approach, although further support through comprehensive training and adequate facilities is still required. Supporting factors include teacher motivation, principal support, and the characteristics of science subjects, while inhibiting factors include limited facilities, variations in student abilities, and insufficient specialized training